2003
DOI: 10.2337/diacare.26.3.832
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Function and the Development of Diabetes-Related Complications in the Diabetes Control and Complications Trial

Abstract: In patients with type 1 diabetes, measurement of connecting peptide (C-peptide), cosecreted with insulin from the islets of Langerhans, permits estimation of remaining ␤-cell secretion of insulin. In this retrospective analysis to distinguish the incremental benefits of residual ␤-cell activity in type 1 diabetes, stimulated (90 min following ingestion of a mixed meal) C-peptide levels at entry in the Diabetes Control and Complications Trial (DCCT) were related to measures of diabetic retinopathy and nephropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
531
2
18

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(584 citation statements)
references
References 24 publications
33
531
2
18
Order By: Relevance
“…This is consistent with previous studies in patients with type 1 diabetes showing a clear relationship between beta cell function and HbA 1c levels during glucose-lowering treatment [27,28]. The mechanisms underling this association have not been completely clarified yet, but may involve the effects of endogenous insulin on alpha cell function [29][30][31] as well as the direct intra-portal drainage of endogenous insulin vs systemic delivery of exogenously administered insulin [32].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies in patients with type 1 diabetes showing a clear relationship between beta cell function and HbA 1c levels during glucose-lowering treatment [27,28]. The mechanisms underling this association have not been completely clarified yet, but may involve the effects of endogenous insulin on alpha cell function [29][30][31] as well as the direct intra-portal drainage of endogenous insulin vs systemic delivery of exogenously administered insulin [32].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, those responders showed a lower risk of diabetic retinopathy and nephropathy than non-responders. A negative relationship between preserved beta cell function and progression of diabetes complications has also been shown in other studies [20][21][22]. Logistic regression analysis showed that decreased C-peptide secretion was a risk for retinopathy and neuropathy in this study.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the DCCT study in which patients with higher beta cell function had a better glucose control and those with a loss of residual beta cell function an increased risk for severe hypoglycaemia [26,27]. In the young placebo subgroup, virtually all patients progressed within 4 years to a metabolic state with wide variability in FBG and with HbA 1c levels >6.5%, despite increased insulin doses.…”
Section: Discussionsupporting
confidence: 85%